Risk Management using Index-Linked Catastrophic Loss Instruments - Gatzert, Nadine; Kellner, Ralf (Zeitschrift für die gesamte Versicherungswissenschaft, 2011)
One way for insurance companies to ensure against high losses due to catastrophic events is the purchase of index-based catastrophic loss instruments. The payoff of these instruments is strongly related to the development of an index, which implies that the degree and type of dependence between the insurer's losses and the index is crucial for their hedging effectiveness. In addition, management strategies on the asset side play an important role for risk management. In this paper, effects of investment decisions and index-based risk transfer instruments on an insurer's solvency capital requirements are investigated with special focus on the impact of the degree and type of dependence between relevant processes.
WiSo-Import:2015-03-26:949
Keywords: -